2012
DOI: 10.1007/s00420-012-0802-4
|View full text |Cite
|
Sign up to set email alerts
|

Urinary creatinine concentrations in an industrial workforce and comparison with reference values of the general population

Abstract: The results of this study correspond well with data from environmental surveys and with recent data from an active workforce in industry with similar sampling strategies. Therefore, a median of 1.4 g creatinine per litre urine seems to be a reasonable value for general calculations and adjustments. The study data also support the validity of the current recommendations by the WHO and several scientific committees and institutions with respect to creatinine limits in spot urine samples for occupational-medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Our study showed that BMI was associated with spot urine creatinine but not with 24-hour urine creatinine. This observation is similar to that reported in two studies [14,24]. Two studies further demonstrated that body mass index was a predictor of spot urine creatinine [24,25], in contrast with our study which showed that body mass index did not predict spot urine creatinine and 24-hour urine creatinine.…”
Section: Spot Urine Creatinine Associated With Bmi In Non-hiv Subjectssupporting
confidence: 92%
“…Our study showed that BMI was associated with spot urine creatinine but not with 24-hour urine creatinine. This observation is similar to that reported in two studies [14,24]. Two studies further demonstrated that body mass index was a predictor of spot urine creatinine [24,25], in contrast with our study which showed that body mass index did not predict spot urine creatinine and 24-hour urine creatinine.…”
Section: Spot Urine Creatinine Associated With Bmi In Non-hiv Subjectssupporting
confidence: 92%
“…Creatinine concentration in urine was analyzed according to a previously described HPLC-UV method. 18 Additionally, blood samples of 7 volunteers (4 women and 3 men, aged 22-56 years) were investigated who participated in an experimental study investigating the human metabolism of PhE. Baseline blood samples of each volunteer (sampling prior to the dosing experiment) were analyzed.…”
Section: Application Of the Methods To Human Samplesmentioning
confidence: 99%